Consumer Legal Protection in Gold Buying and Selling Transactions at Bank Syariah Indonesia Aksara Medan - Suprayitno, Suprayitno; Tony, Tony (Lafadz Jaya Publisher, 2024)
The rules in the consumer protection law No. 8 of 1999 in buying and selling transactions regarding buying and selling law analyze how consumer protection rules and economic law, especially sharia-based concepts, apply to Indonesian sharia banks. The type of research is qualitative with a normative juridical and empirical juridical research approach, collecting data, rules/regulations, and in reality, in practice in the field where the research was carried out, namely at Indonesian sharia banks, with data collection techniques used namely library research and interview. The research results show that Indonesian sharia banks are one of the sales places for buying gold, where customers can carry out gold buying and selling transactions anywhere and anytime from mobile banking. Furthermore, consumers/customers who feel disadvantaged by Indonesian sharia banks can report to the partyCivil Servant Investigator (PPNS) ITE Directorate of Information Security, and the form of supervision by CoFTRA, namely preventive supervision then repressive supervision. The implementation of consumer protection at Indonesian sharia banks focuses on 2 things, including returning the product (return) and returning the funds (refund). Implementation of consumer protection for Indonesian sharia banks in accordance with the UUPK, where the bank has given its rights to its consumers in accordance with the provisions contained in the UUPK. Meanwhile, its application in the view/perspective of Sharia Economic Law is appropriate from the point of view of consumer rights in Islamic rules, Indonesian sharia banks provide khiyar rights (cancel/continue the sale and purchase agreement) if there is an error/mistake by the bank. The resolution if there is a dispute chosen by the Indonesian sharia bank is through peace and resolving it internally, this is in accordance with the concepts of Islamic buying and selling.